USM TO CREATE A UNIVERSAL RESEARCH ECOSYSTEM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, April 2015 – Research is for all and should not be restricted to certain parties. As such, the initiative "Young Strategic Thinkers For USM Future" by Universiti Sains Malaysia (USM) is an excellent platform to generate ideas in order to drive excellence for the future of the university.